Role of SST, CORT and ghrelin and its receptors at the endocrine pancreas - Chanclón, Belen; Martínez-Fuentes, Antonio J; Gracia-Navarro, Francisco (Frontiers in Endocrinology, 2012)
Somatostatin (SST), cortistatin (CORT), and its receptors (sst1-5), and ghrelin and its receptors (GHS-R) are two highly interrelated neuropeptide systems with a broad range of overlapping biological actions at central, cardiovascular and immune levels among others. Besides their potent regulatory role on GH release, its endocrine actions are highlighted by SST/CORT and ghrelin influence on insulin secretion, glucose homeostasis and insulin resistance. Interestingly, most components of these systems are expressed at the endocrine pancreas and are actively involved in the modulation of pancreatic islet function and, consequently influence glucose homeostasis. In addition, some of them also participate in islet survival and regeneration. Furthermore, under severe metabolic condition as well as in endocrine pathologies, their expression profile is severely deregulated. These finding suggest that SST/CORT and ghrelin systems could play a relevant role in pancreatic function under metabolic and endocrine pathologies. Accordingly, these systems have been therapeutically targeted for the prevention or amelioration of certain metabolic conditions (obesity) as well as for tumor growth inhibition and/or hormonal regulation in endocrine pathologies (neuroendocrine tumors). This review focuses on the interrelationship between SST/CORT and ghrelin systems and their role in severe metabolic conditions and some endocrine disorders.